Method for obtaining interface properties of ceramic matrix composites based on tensile hysteresis loop
By conducting a one-way tensile loading and unloading experiment on ceramic matrix composite materials, tensile stress strain hysteresis loops were obtained, and interface performance and axial thermal residual stress were calculated through the two-step method, which solved the problem that the existing technology could not fully obtain interface performance and axial thermal residual stress, and achieved high-precision interface performance testing.
Patent Information
- Application Number
- CN202411703395.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing interface performance testing methods for ceramic matrix composite materials cannot fully obtain interface performance and axial thermal residual stress, and cannot consider the Poisson effect.
By conducting a one-way tensile loading and unloading experiment on ceramic matrix composites, tensile stress-strain hysteresis loops were obtained. Combined with the hysteresis modulus, plastic strain and hysteresis width, the Coulon friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress were iteratively calculated using a two-step method.
It realizes accurate acquisition of the interface performance and axial thermal residual stress of ceramic matrix composite materials, overcomes the limitations of the prior art, and improves the accuracy of multi-parameter fitting.
Smart Images

Figure CN119198337B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic matrix composite material interface performance testing, and in particular to a method for obtaining ceramic matrix composite material interface performance based on a tensile hysteresis loop. Background Art
[0002] Ceramic matrix composites have broad application potential in aeroengines, hypersonic vehicles, and nuclear engineering due to their light weight, high strength, and superior high-temperature mechanical properties. Compared with the inherent brittleness of single ceramics, ceramic matrix composites exhibit significant pseudo-plastic characteristics due to their carefully designed microstructures. A large number of experimental and theoretical studies have shown that the key to pseudo-plastic behavior lies in the deflection of matrix cracks at the interface and the subsequent interfacial debonding and slip. Therefore, the interface properties are crucial to the macroscopic mechanical properties of ceramic matrix composites, and accurate interface characterization is of great significance for their practical applications.
[0003] The existing interface characterization methods can be mainly divided into four types: micro-column compression method, single fiber push-in / pull-out method, saturated matrix crack spacing method and tensile hysteresis loop method. Microscopic testing methods, such as micro-column compression method and fiber push-in / pull-out method, can directly reflect the interface performance, but the sample preparation and testing process are complicated, and can only capture local performance and cannot represent the overall behavior. In contrast, the saturated matrix crack spacing method is more convenient in measuring saturated crack spacing and deriving interface friction stress. However, due to the limitations of model assumptions, this method can only be used to characterize constant interface friction stress, cannot consider Poisson's effect, and cannot provide necessary additional parameters such as Coulomb friction coefficient, interface debonding toughness and other interface properties and axial thermal residual stress.
[0004] Therefore, it is desired to have a technical solution to overcome or at least alleviate at least one of the above-mentioned defects of the prior art. Summary of the invention
[0005] The object of the present invention is to provide a method for obtaining the interface properties of ceramic matrix composite materials based on a tensile hysteresis loop to overcome or at least alleviate at least one of the above-mentioned defects of the prior art.
[0006] To achieve the above object, the present invention provides a method for obtaining the interface properties of a ceramic matrix composite material based on a tensile hysteresis loop, and the method for obtaining the interface properties of a ceramic matrix composite material based on a tensile hysteresis loop comprises:
[0007] The uniaxial tensile loading and unloading test is carried out on the ceramic matrix composite material, so as to obtain the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses;
[0008] According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the hysteresis width of the tensile stress-strain hysteresis loop under different peak stresses and the loading and unloading stress, the hysteresis modulus and the plastic strain are obtained;
[0009] According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress is obtained;
[0010] According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, it is judged whether it meets the situation of small debonding energy. If so, based on the expression of plastic strain, the expression of hysteresis modulus and the expression of hysteresis width, according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured by uniaxial tensile loading and unloading experiments and the loading and unloading stress, a two-step method is used to iteratively calculate the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material.
[0011] Optionally, the method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop further comprises:
[0012] According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, it is judged whether it meets the condition of small debonding energy. If not, then
[0013] The optimization algorithm is used to iteratively calculate the interface properties and axial thermal residual stress simultaneously.
[0014] Optionally, the expression based on plastic strain, the expression based on hysteresis modulus and the expression based on hysteresis width, according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured by uniaxial tensile loading and unloading experiments and the loading and unloading stress, adopts a two-step method to iteratively calculate the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material, respectively, including:
[0015] Step 1: Using an optimization algorithm, the hysteresis modulus of the tensile stress-strain hysteresis loop under different peak stresses and the hysteresis width of the hysteresis loop measured by uniaxial tensile loading and unloading experiments are numerically iterated based on the expression of the hysteresis modulus and the expression of the hysteresis width, so as to obtain the Coulomb friction coefficient and the initial interface radial pressure of the ceramic matrix composite material;
[0016] Step 2: Based on the Coulomb friction coefficient and initial interface radial pressure of the ceramic matrix composite material, the optimization algorithm is continued to be used to numerically iterate the plastic strain of the tensile stress-strain hysteresis loop measured by the uniaxial tensile loading and unloading experiment and the theoretical prediction results obtained by the expression based on the plastic strain, so as to obtain the interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material.
[0017] Optionally, the iterative calculation of the interface performance and the axial thermal residual stress simultaneously using the optimization algorithm includes:
[0018] Based on the optimization algorithm, the plastic strain, hysteresis modulus and hysteresis width of the tensile stress-strain hysteresis loop under different peak stresses measured in the uniaxial tensile loading and unloading experiment are numerically iterated simultaneously based on various expressions to obtain the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material; wherein, the various expressions include the expression of plastic strain, the expression of hysteresis modulus and the expression of hysteresis width.
[0019] Optionally, the expression of the plastic strain is as follows:
[0020] ;in,
[0021] is the plastic strain of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, R f is the fiber radius, E f is the Young's modulus of the fiber, a f is the thermal expansion coefficient of the fiber, is the thermal residual stress in the fiber axial direction, is the temperature difference between the preparation temperature and the service temperature of the composite material, l d is the interface debonding length, l umax is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 5 and w It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0022] Optionally, the expression of the hysteresis modulus is as follows:
[0023] ;in,
[0024] E h is the hysteresis modulus of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, is the peak stress, c f is the fiber volume fraction, R f is the fiber radius, E f is the Young's modulus of the fiber, l d is the interface debonding length, l umax is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 2. w and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0025] Optionally, the expression of the hysteresis width is as follows:
[0026] ;in,
[0027] is the hysteresis width of the tensile stress-strain hysteresis loop at any loading and unloading stress level, is the strain of the composite material during unloading, is the strain of the composite material during reloading, For external stress, is the critical external stress during interface peeling, R f is the fiber radius, E f is the Young's modulus of the fiber, l d is the interface debonding length, l u is the interface reverse slip length, l r is the interface reslip length, l umaxis the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1 and w It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0028] The present invention can accurately obtain the interface properties and axial thermal residual stress of ceramic matrix composite materials by analyzing the tensile stress-strain hysteresis loop. On the one hand, it overcomes the limitations of the existing tensile hysteresis loop test method that can only obtain constant friction stress, cannot consider the Poisson effect, and cannot fully obtain the interface properties and axial thermal residual stress of the composite material.
[0029] On the other hand, for common ceramic-based composites with "weak interface and thin interface layer", small debonding phenomenon is more common; therefore, the "two-step method" acquisition process proposed in the present invention significantly improves the accuracy of multi-parameter fitting by decoupling the fitting process of multiple unknown performance parameters, providing an important reference for comprehensively evaluating the interface properties of such composites and predicting their macroscopic mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Also, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings,
[0031] Figure 1 It is a brief flow chart of a method for obtaining the interface properties of ceramic matrix composite materials based on a tensile hysteresis loop in one embodiment of the present invention.
[0032] Figure 2 yes Figure 1 The specific process diagram of the method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop is shown.
[0033] Figure 3 This is a calculation result diagram of the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress of the ceramic matrix composite material under different peak stresses.
[0034] Figure 4 It is a schematic diagram of the hysteresis loop of ceramic matrix composite materials and the characteristic parameters that characterize its shape and position.
[0035] Figure 5It is a comparison chart between theoretical prediction results and experimental results of stress-strain curves of ceramic matrix composites during tensile loading, unloading and reloading. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. In the drawings, the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The described embodiments are part of the embodiments of the present invention, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limitations on the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The embodiments of the present invention are described in detail below in conjunction with the drawings.
[0037] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the scope of protection of the present invention.
[0038] Since there are many parameters in the present invention, in order to facilitate the understanding of the present invention, the meanings, symbols and acquisition methods of the parameters involved in the present invention are first explained, as shown in the following table:
[0039]
[0040] In the present embodiment, the parameters obtained by the experiment are mainly divided into three categories. The first category is basic performance parameters, including fiber volume fraction, fiber radius, fiber modulus, fiber thermal expansion coefficient and temperature difference during the preparation process, which are usually provided by personnel related to material preparation. The second category of parameters can be directly obtained in the unidirectional tensile loading and unloading experiment on which the present invention relies, including external stress, peak stress, saturated matrix crack spacing, etc. during unidirectional tensile loading, unloading and reloading. The third category of parameters needs to be fitted based on the test results of the unidirectional tensile loading and unloading experiment, including interface debonding toughness, Coulomb friction coefficient, initial interface radial pressure, thermal residual stress, matrix characteristic strength and matrix Weibull modulus, etc. It can be understood that the above experiments are all existing experiments, and the specific experimental process will not be repeated here.
[0041] like Figure 1 and Figure 2 The method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop includes:
[0042] Step 1: Perform uniaxial tensile loading and unloading experiments on the ceramic matrix composite material to obtain the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses;
[0043] Step 2: According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the hysteresis width of the tensile stress-strain hysteresis loop under different peak stresses and the loading and unloading stress, the hysteresis modulus and the plastic strain are obtained;
[0044] Step 3: According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress is obtained;
[0045] Step 4: According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, determine whether it meets the situation of small debonding energy. If so, based on the expression of plastic strain, the expression of hysteresis modulus and the expression of hysteresis width, according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured in the uniaxial tensile loading and unloading experiment and the loading and unloading stress, a two-step method is used to iteratively calculate the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material.
[0046] In this embodiment, the method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop further includes:
[0047] Step 5: Based on the expressions of plastic strain, hysteresis modulus and hysteresis width, and according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured in the uniaxial tensile loading and unloading test and the loading and unloading stress, a two-step method is used to iteratively calculate the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material.
[0048] In this embodiment, the method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop further includes:
[0049] Step 6: According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, determine whether it meets the condition of small debonding energy. If not, then
[0050] Step 7: Use the optimization algorithm to iteratively calculate the interface performance and axial thermal residual stress simultaneously.
[0051] In this embodiment, the ceramic matrix composite material of the present invention is a unidirectional fiber reinforced ceramic matrix composite material, the fiber represents the fiber in the unidirectional fiber reinforced ceramic matrix composite material, the matrix represents the ceramic matrix in the unidirectional fiber reinforced ceramic matrix composite material, and the interface represents the interface between the fiber and the interface layer in the unidirectional fiber reinforced ceramic matrix composite material.
[0052] In this embodiment, C f / PyC / SiC fiber reinforced ceramic matrix composite material is the test sample, the thickness of PyC (pyrolytic carbon) interface layer is 300 nm, the test environment temperature is 25 ℃, and other basic performance parameters of the test sample obtained through basic mechanical properties test are as follows:
[0053] MPa.
[0054] In this embodiment, the uniaxial tension refers to axial tensile loading of the uniaxial fiber reinforced ceramic matrix composite material; the uniaxial tensile loading and unloading experiment refers to axial tensile loading of the uniaxial fiber reinforced ceramic matrix composite material, and unloading and reloading in sequence under a certain peak stress; the peak stress refers to the maximum stress value reached at a certain moment before unloading and reloading in sequence during the axial tensile loading of the unidirectional fiber reinforced ceramic matrix composite material.
[0055] In this embodiment, the tensile stress-strain hysteresis loop refers to a closed stress-strain curve formed by unloading and reloading in sequence, starting from a peak stress point higher than the matrix cracking stress, during the axial tensile loading process of the unidirectional fiber reinforced composite material.
[0056] In this embodiment, the unloading refers to the process of gradually reducing the external stress applied to the ceramic-based composite material from the peak stress to zero; the reloading refers to the process of gradually increasing the external stress applied from zero to the peak stress again after the ceramic-based composite material is completely unloaded.
[0057] In this embodiment, during the unloading process, the rate of stress reduction is preferably 0.01 MPa / s; during the reloading process, the rate of stress increase is preferably 0.01 MPa / s.
[0058] In this embodiment, the relationship between the tangent modulus of the tensile stress-strain hysteresis loop and the loading and unloading stress can be obtained by the following method:
[0059] Based on the least squares method, a polynomial fitting is performed on the tensile stress-strain hysteresis loop formed by unloading and reloading of ceramic matrix composites under different peak stresses to determine the unknown parameters in the polynomial. Then, by solving the first-order derivative of the polynomial, the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress is obtained.
[0060] In this embodiment, the small debonding energy condition means that during the unloading process, the interface reverse slip length is always less than the interface debonding length; conversely, when the small debonding energy condition is not met, it is called a large debonding energy condition; the large debonding energy condition means that during the unloading process, the interface can reversely slip to the debonding tip, that is, the maximum interface reverse slip length is equal to the interface debonding length.
[0061] In this embodiment, the following method is preferably used to determine whether the condition of small debonding energy is met based on the relationship between the tangent modulus and the loading and unloading stress:
[0062] During unloading or reloading, when the tangent modulus decreases monotonically with decreasing or increasing stress level, it is considered to be a case of small debonding energy; if the tangent modulus decreases monotonically first and then tends to be horizontal when the stress level decreases or increases, it is considered to be a case of large debonding energy. Figure 3 As shown, at different peak stress levels, the tangent modulus of the hysteresis loop of the test sample maintains a corresponding monotonic change trend during unloading and reloading, so it can be considered as a small debonding energy case.
[0063] In this embodiment, the present invention calculates characteristic parameters that can characterize the position and shape of the hysteresis loop under different peak stresses based on the basic performance parameters of the ceramic matrix composite material; the characteristic parameters are as follows: Figure 4 As shown, it specifically includes: plastic strain, hysteresis modulus and hysteresis width. In the present invention, the plastic strain of one of the characteristic parameters of the tensile stress-strain hysteresis loop is as shown in Formula 1:
[0064] Formula 1,
[0065] in, is the plastic strain of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, R f is the fiber radius, E f is the Young's modulus of the fiber, a f is the thermal expansion coefficient of the fiber, is the thermal residual stress in the fiber axial direction, is the temperature difference between the preparation temperature and the service temperature of the composite material, l d is the interface debonding length,l umax is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 5 and w It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0066] In this embodiment, the hysteresis modulus, one of the characteristic parameters of the tensile stress-strain hysteresis loop, is shown in Formula 2:
[0067] Formula 2,
[0068] in, E h is the hysteresis modulus of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, is the peak stress, c f is the fiber volume fraction, R f is the fiber radius, E f is the Young's modulus of the fiber, l d is the interface debonding length, l umax is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 2. w and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0069] In this embodiment, the hysteresis width, which is one of the characteristic parameters of the hysteresis loop, is shown in Formula 3:
[0070] Formula 3,
[0071] in, is the hysteresis width of the tensile stress-strain hysteresis loop at any loading and unloading stress level, is the strain of the composite material during unloading, is the strain of the composite material during the reloading process, For external stress, is the critical external stress during interface peeling, R f is the fiber radius, E f is the Young's modulus of the fiber, l d is the interface debonding length, l r is the interface reverse slip length, l r is the interface reslip length, l umax is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1 and w It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0072] In this embodiment, the conjugate length associated with the interfacial slip friction in the debonding region is l Use the following formula to obtain:
[0073] Formula 4,
[0074] in, is the Coulomb friction coefficient on the debonding interface, R f is the fiber radius, k 1 is a dimensionless parameter related to the physical or geometric properties of the component material.
[0075] In this embodiment, the critical external stress during interface peeling is Use the following formula to obtain:
[0076] Formula 5,
[0077] in, is the initial interface radial pressure (related to the radial thermal residual stress at the interface and the additional radial stress caused by the interface roughness), c f is the fiber volume fraction, k 1 and k 2 is a dimensionless parameter related to the physical or geometric properties of the component materials.
[0078] In this embodiment, the fiber axial thermal residual stress Use the following formula to obtain:
[0079] Formula 6,
[0080] in, is the equivalent axial thermal residual stress of the composite material, c f is the fiber volume fraction, and is a dimensionless parameter related to the physical or geometric properties of the component materials, It is the temperature difference between the preparation temperature and the service temperature of the composite material.
[0081] In this embodiment, the present invention uses a fracture mechanics method to obtain the interface debonding length of the ceramic matrix composite material during uniaxial tensile loading. l d Preferably, the relationship shown in Formula 7 is used to obtain:
[0082] Formula 7,
[0083] in, The interface debonding toughness, E f is the Young's modulus of the fiber, R f is the fiber radius, c f is the fiber volume fraction, e is a natural constant, is a dimensionless parameter related to the matrix crack spacing, , and It is a dimensionless parameter related to the component material or external stress.
[0084] In this embodiment, the present invention determines the interface slip length during unloading and reloading based on the condition that the relative displacement between the fiber and the matrix near the interface debonding tip remains unchanged during unloading and reloading; the interface slip length includes the interface reverse slip length and the re-slip length.
[0085] In this embodiment, the interface reverse slip length l u Preferably, the relationship shown in Formula 8 is used to obtain:
[0086] Formula 8,
[0087] in, ld is the interface debonding length, is the conjugate length associated with the interfacial slip friction in the debonding region, is the peak stress, is the external stress during unloading, c f is the fiber volume fraction, e is a natural constant, w and It is a dimensionless parameter related to the physical or geometric properties of the component materials. Maximum interface reverse slip length l umax Through Lianli And formula 8 to get.
[0088] The interface reslip length l r Preferably, the relationship shown in formula 9 is used to obtain:
[0089] Formula 9,
[0090] in, l umax is the maximum interface reverse slip length during unloading, l d is the interface debonding length, is the conjugate length associated with the interfacial slip friction in the debonding region, is the critical external stress during interface peeling, is the external stress during the reloading process, c f is the fiber volume fraction, e is a natural constant, w and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0091] In this embodiment, the present invention is based on the matrix random cracking model and adopts Weibull distribution to describe the evolution of matrix cracks during loading, so as to obtain the matrix crack spacing at different peak stress levels. L Preferably, the relationship shown in formula 10 is used to obtain:
[0092] Formula 10,
[0093] in, L sat is half the crack spacing of the saturated matrix. is the peak stress, is the matrix cracking stress, is the characteristic strength of the matrix, is the Weibull modulus of the matrix.
[0094] In this embodiment, the dimensionless parameters related to the physical properties, geometric properties, external stress, matrix crack spacing and bonding area interface shear stiffness of the component materials are preferably calculated using a shear lag model. Specifically, these parameters can be calculated using the relevant formulas in the paper "Effect of interphase layer onmatrix cracking in fiber reinforced ceramic matrix composites" published by Xiaochuan Niu et al. The present invention has no special requirements for the numerical calculation method of these parameters, and can be carried out in a manner familiar to those skilled in the art, including but not limited to programming languages such as Matlab or Python.
[0095] In this embodiment, according to Figure 3 It can be judged that when the peak stress is 498 MPa, 588 MPa and 643 MPa, the test samples all belong to the small debonding energy case. Therefore, the present invention adopts a two-step method to iteratively calculate the Coulomb friction coefficient, the initial interface radial pressure, the interface debonding toughness and the axial thermal residual stress.
[0096] The specific steps of obtaining the interface properties and thermal residual stress using the two-step method include:
[0097] Step 1: Given the initial values of the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness, and axial thermal residual stress (the initial value can be set as needed), calculate the theoretically predicted hysteresis modulus and hysteresis width using Equations 2 and 3. If the error between the theoretically predicted values and the experimental results of the hysteresis modulus and hysteresis width is less than the required accuracy, the iteration is completed; otherwise, the values of the Coulomb friction coefficient and the initial interface radial pressure are updated according to the optimization algorithm, and then the above process is repeated until the iteration is completed, thereby obtaining the Coulomb friction coefficient of the ceramic matrix composite material. and the initial interface radial pressure 0.36±0.3 and MPa.
[0098] Step 2: Based on the Coulomb friction coefficient and initial interface radial pressure of the ceramic matrix composite material, the initial values of the interface debonding toughness and axial thermal residual stress are given (the initial value can be set as needed), and the theoretically predicted plastic strain is calculated by formula 1. If the error between the theoretical predicted value of the plastic strain and the experimental result is less than the required accuracy, the iteration is completed; otherwise, the values of the interface debonding toughness and axial thermal residual stress are updated according to the optimization algorithm, and then the above process is repeated until the iteration is completed, thereby obtaining the interface debonding toughness of the ceramic matrix composite material. and axial thermal residual stress 0.165±0.035 N / m and MPa.
[0099] In this embodiment, if the test sample belongs to the case of large debonding energy, it is necessary to iteratively calculate the interface performance and thermal residual stress at the same time. The specific steps of iteratively calculating the required parameters at the same time include:
[0100] Given the initial values of the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness, and axial thermal residual stress (the initial value can be set as needed), the theoretically predicted plastic strain, hysteresis modulus, and hysteresis width are calculated by equations 1, 2, and 3. If the error between the theoretically predicted values and the experimental results of the plastic strain, hysteresis modulus, and hysteresis width is less than the required accuracy, the iteration is completed; otherwise, the values of the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness, and axial thermal residual stress are updated according to the optimization algorithm, and then the above process is repeated until the iteration is completed.
[0101] In this embodiment, the optimization algorithm refers to an algorithm used to fit experimental data to obtain interface performance and thermal residual stress; this embodiment adopts a genetic algorithm, and the optimization algorithms that can be used include but are not limited to particle swarm optimization algorithms and other optimization algorithms suitable for this purpose.
[0102] In this example, in order to verify the rationality of the method of the present invention, based on the obtained interface properties and thermal residual stress parameters, the tensile curves during uniaxial tensile loading, unloading and reloading were obtained by theoretical prediction and calculation, and compared with the experimental results. The stress-strain relationship of the composite material during uniaxial tensile loading predicted by the theory is shown in Formula 11:
[0103] Formula 11,
[0104] in, is the strain of the composite material during uniaxial tensile loading, is the external stress during uniaxial tensile loading, is the critical external stress during interface peeling, l d is the interface debonding length, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. c f is the fiber volume fraction, R f is the fiber radius, E f is the Young's modulus of the fiber, a fis the thermal expansion coefficient of the fiber, is the temperature difference between the preparation temperature and the service temperature of the composite material, is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a i ( i =1,2,5), w , and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0105] The stress-strain relationship of the composite material during unloading predicted by the theory is shown in Equation 12:
[0106] Formula 12,
[0107] in, is the strain of the composite material during unloading, is the external stress during unloading, is the critical external stress during interface peeling, l d is the interface debonding length, l u is the interface reverse slip length, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. c f is the fiber volume fraction, R f is the fiber radius, E f is the Young's modulus of the fiber, a f is the thermal expansion coefficient of the fiber, is the temperature difference between the preparation temperature and the service temperature of the composite material, is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a i ( i =1,2,5), w , and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0108] The stress-strain relationship of the composite material during the reloading process predicted by the theory is shown in Equation 13:
[0109] Formula 13,
[0110] in, is the strain of the composite material during the reloading process, is the external stress during the reloading process, is the critical external stress during interface peeling, l d is the interface debonding length, l r is the interface reslip length, l umax is the maximum interface reverse slip length during unloading, L is half of the matrix crack spacing. is the conjugate length associated with the interfacial slip friction in the debonding region, c f is the fiber volume fraction, R f is the fiber radius, E f is the Young's modulus of the fiber, a f is the fiber thermal expansion coefficient, is the temperature difference between the preparation temperature and the service temperature of the composite material, is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a i ( i =1,2,5), w , and It is a dimensionless parameter related to the physical or geometric properties of the component material.
[0111] from Figure 5 It can be seen that the stress-strain relationship of the ceramic matrix composite material during uniaxial tensile loading, unloading and reloading, including the characteristic parameters of the hysteresis loop such as plastic strain, hysteresis modulus and hysteresis width, calculated by the method for obtaining the interface properties of the ceramic matrix composite material based on the tensile hysteresis loop provided by the present invention, is in good agreement with the experimental results. This further verifies the feasibility and accuracy of the present method in obtaining interface properties and thermal residual stress.
[0112] The present invention provides a method for obtaining the interface properties of ceramic-based composite materials based on a tensile hysteresis loop. First, the present invention obtains key parameters such as plastic strain, hysteresis modulus and hysteresis width according to the experimentally measured composite material hysteresis loop. Secondly, the tangent modulus of the tensile stress-strain hysteresis loop of the material during unloading and reloading is calculated to analyze the debonding and slippage of the interface; if the relationship between the tangent modulus and the loading and unloading stress conforms to the characteristics of the small debonding energy situation, a two-step method is used to obtain the interface properties and thermal residual stress of the ceramic-based composite material; if it conforms to the characteristics of the large debonding energy situation, the interface properties and thermal residual stress are iteratively calculated simultaneously. Based on the tensile stress-strain hysteresis loop, the present invention can accurately obtain the interface properties and thermal residual stress of ceramic-based composite materials, providing an important reference for comprehensively evaluating the interface properties of such composite materials and predicting their macroscopic mechanical properties.
[0113] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims of the present invention.
[0114] Finally, it should be pointed out that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for obtaining the interface properties of ceramic matrix composite materials based on tensile hysteresis loop, characterized in that: The method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop comprises: The uniaxial tensile loading and unloading test is carried out on the ceramic matrix composite material, so as to obtain the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses; According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the hysteresis width of the tensile stress-strain hysteresis loop under different peak stresses and the loading and unloading stress, the hysteresis modulus and the plastic strain are obtained; According to the tensile stress-strain hysteresis loop formed by unloading and reloading the ceramic matrix composite material under different peak stresses, the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress is obtained; According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, it is judged whether it meets the situation of small debonding energy. If so, based on the expression of plastic strain, the expression of hysteresis modulus and the expression of hysteresis width, according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured by uniaxial tensile loading and unloading experiments and the loading and unloading stress, a two-step method is used to iteratively calculate the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material respectively; wherein, the situation of small debonding energy refers to that during the unloading process, the interface reverse slip length is always less than the interface debonding length; The expression based on plastic strain, the expression based on hysteresis modulus and the expression based on hysteresis width, according to the relationship between the plastic strain, hysteresis modulus and hysteresis width of the hysteresis loop under different peak stresses measured in the uniaxial tensile loading and unloading experiment and the loading and unloading stress, adopts a two-step method to iteratively calculate the Coulomb friction coefficient, the initial interface radial pressure, the interface debonding toughness and the axial thermal residual stress of the ceramic matrix composite material respectively, including: Step 1: Using an optimization algorithm, the hysteresis modulus of the tensile stress-strain hysteresis loop under different peak stresses and the hysteresis width of the hysteresis loop measured by uniaxial tensile loading and unloading experiments are numerically iterated based on the expression of the hysteresis modulus and the expression of the hysteresis width, so as to obtain the Coulomb friction coefficient and the initial interface radial pressure of the ceramic matrix composite material; Step 2: Based on the Coulomb friction coefficient and initial interface radial pressure of the ceramic matrix composite material, the optimization algorithm is continued to be used to numerically iterate the plastic strain of the tensile stress-strain hysteresis loop measured by the uniaxial tensile loading and unloading test and the theoretical prediction results obtained by the expression based on the plastic strain, so as to obtain the interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material; The expression of plastic strain is as follows: , in, is the plastic strain of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, is the fiber radius, is the Young's modulus of the fiber, is the thermal expansion coefficient of the fiber, is the thermal residual stress in the fiber axial direction, is the temperature difference between the preparation temperature and the service temperature of the composite material, is the interface debonding length, is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 5 and is a dimensionless parameter related to the physical or geometric properties of the component materials; The expression of the hysteresis modulus is as follows: , in, is the hysteresis modulus of the tensile stress-strain hysteresis loop, is the critical external stress during interface peeling, is the peak stress, is the fiber volume fraction, is the fiber radius, is the Young's modulus of the fiber, is the interface debonding length, is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1. a 2. and is a dimensionless parameter related to the physical or geometric properties of the component materials; The expression of the hysteresis width is as follows: , in, is the hysteresis width of the tensile stress-strain hysteresis loop at any loading and unloading stress level, is the strain of the composite material during unloading, is the strain of the composite material during reloading, For external stress, is the critical external stress during interface peeling, is the fiber radius, is the Young's modulus of the fiber, is the interface debonding length, is the interface reverse slip length, is the interface reslip length, is the maximum interface reverse slip length during unloading, is the conjugate length associated with the interfacial slip friction in the debonding region, L is half of the matrix crack spacing. is a dimensionless parameter related to the interfacial shear stiffness of the bonding area, e is a natural constant, a 1 and It is a dimensionless parameter related to the physical or geometric properties of the component material.
2. The method for obtaining the interface properties of ceramic matrix composite materials based on tensile hysteresis loop according to claim 1, characterized in that: The method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop further comprises: According to the relationship between the tangent modulus of the hysteresis loop and the loading and unloading stress, it is judged whether it meets the condition of small debonding energy. If not, then The optimization algorithm is used to iteratively calculate the interface properties and axial thermal residual stress simultaneously.
3. The method for obtaining the interface properties of ceramic matrix composite materials based on the tensile hysteresis loop according to claim 2, characterized in that: The iterative calculation of the interface performance and the axial thermal residual stress simultaneously by using the optimization algorithm includes: Based on the optimization algorithm, the plastic strain, hysteresis modulus and hysteresis width of the tensile stress-strain hysteresis loop under different peak stresses measured in the uniaxial tensile loading and unloading experiment are numerically iterated simultaneously based on various expressions to obtain the Coulomb friction coefficient, initial interface radial pressure, interface debonding toughness and axial thermal residual stress of the ceramic matrix composite material; wherein, the various expressions include the expression of plastic strain, the expression of hysteresis modulus and the expression of hysteresis width.
Citation Information
Patent Citations
Prediction method for fatigue hysteresis loop of woven ceramic matrix composite material by considering matrix and fiber breakage
CN113032982A
Method for predicting thermal residual stress and thermal residual strain of fiber reinforced ceramic matrix composite material through hysteresis loop
CN115203965A